Pengaruh Liliterasi Digital dan Orientasi Kewirausahaan Terhadap Kinerja Usaha UMKM di Kota Bandung - Agil, Mohammad Septo; Apriadi, Deri (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze the effect of digital literacy and entrepreneurial orientation on the business performance of MSMEs in Bandung City. A quantitative approach was applied using descriptive and verificative methods to describe empirical phenomena and test causal relationships between variables. Data were collected through questionnaires distributed to 201 MSME owners, selected using an accidental sampling technique. Data analysis employed multiple linear regression with the assistance of SPSS software. The results indicate that digital literacy and entrepreneurial orientation simultaneously have a significant effect on business performance, with a coefficient of determination (R²) of 0.716, meaning that 71.6% of performance variation is explained by both variables. Partially, digital literacy shows a more dominant influence than entrepreneurial orientation. These findings confirm that the ability of MSME actors to utilize digital technology and integrate it with entrepreneurial values plays a crucial role in enhancing efficiency, innovation, and competitiveness in the digital transformation era.